2019
DOI: 10.3390/nano9030434
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Self-Healing Graphene-Nanoplate/Polyurethane Nanocomposites via Diels–Alder Reaction through a One-Shot Process

Abstract: Thermally self-healing graphene-nanoplate/polyurethane (GNP/PU) nanocomposites were prepared via a bulk in-situ Diels–Alder (DA) reaction. Graphene-nanoplate (GNP) was used as a reinforcement and crosslinking platform by a DA reaction with a furfuryl-based chain extender of polyurethane (PU). Results showed that a DA reaction occurred in GNP during the PU forming cure process. This procedure is simple and solvent free because of the absence of any independent surface modification process. Through the calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…When this relationship is satisfied, a DA reaction can occur between the GNPs and FA since FA will be located close to the GNP surface. In a previous study, we confirmed an in-situ DA reaction between GNPs and furfuryl derivative for nanocomposites comprising polyurethane and GNPs [42]. The surface tension values and their components can be calculated based on the relationship between the Young and Wu equations.…”
Section: Resultssupporting
confidence: 67%
“…When this relationship is satisfied, a DA reaction can occur between the GNPs and FA since FA will be located close to the GNP surface. In a previous study, we confirmed an in-situ DA reaction between GNPs and furfuryl derivative for nanocomposites comprising polyurethane and GNPs [42]. The surface tension values and their components can be calculated based on the relationship between the Young and Wu equations.…”
Section: Resultssupporting
confidence: 67%
“…The infrared images clearly exhibit uniform color distribution over the composite film, indicating the uniform temperature distribution across the composite film. Before studying the self-healing of the G-TPU composite films via electricity and IR light, we studied the electro-thermal response and IR thermal response performances of the G-TPU composite films [5][6][7][31][32][33][34][35]. The electro-thermal response performance of the composite films were studied by applying direct current to the composite films in a laboratory environment.…”
Section: Electro-thermal Response and Ir Thermal Response Performancementioning
confidence: 99%
“…This is largely due to their excellent comprehensive properties, such as high strength, high toughness, abrasion resistance and oil resistance, and good processing performance [1][2][3][4]. However, they are susceptible to failure arising from micro-cracks generated on the surface and inside inner layer during processing and utilization, which lead to a sharp decrease in their sustainability, safety, and lifetime [5][6][7][8][9]. To solve this problem, self-healing polymers and composites that can heal themselves spontaneously and automatically in response to damage and regenerate its original structure and function, have gradually become a research hotspot [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of electronics, communication, and artificial intelligence industry, flexible conductive composites have attracted extensive attention in academia and industry due to its portability, good biological compatibility, and stretchability and are widely used in sensors, flexible displays, energy devices, medical electronics and integrated circuit, and so on [ 1 , 2 , 3 , 4 , 5 ]. At present, flexible conductive composite materials are usually composed of polymer materials and conductive nanomaterials [ 4 , 5 , 6 , 7 , 8 ]. Polymer materials, such as epoxy, polyimide, and polyurethane, as flexible substrates are mostly insulators and do not have electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%